Perancangan Sistem Pakar Berbasis Web Menggunakan Case Based Reasoning Untuk Diagnosa Dini Covid-19 - Mega Lumbia Sinaga; Dudih Gustian; Falentino Sembiring (STMIK Banjarbaru, 2021)
AbstrackThe COVID-19 pandemic has a profound impact on many aspects of people's lives. Various ways are being sought to help resolve the spread of COVID 19. The addition of new symptoms that have continued to vary from the beginning to the present has made the public more and more anxious. The symptoms that are felt are usually difficult for the general public to self-diagnose, making it difficult for the public to take preventive action. This paper presents a Web-based expert system model to diagnose Covid-19 early using the Case Based Reasoning Method to help the public diagnose Covid 19 early. Application testing is carried out by comparing the diagnostic results of expert system applications with expert opinions. The test results on 6 sample cases show that the application can diagnose all cases according to expert opinion.Keywords: Expert System, COVID-19, Case Based ReasoningAbstrakPandemi COVID-19 menimbulkan dampak bagi banyak sendi kehidupan kemasyarakat. Berbagai cara diupayakan untuk membantu menyelesaikan penyebaran COVID 19. Bertambahnya gejala-gejala baru yang terus bervariasi sejak awal hingga saat ini membuat masyarakat semakin was-was. Gejala-gejala yang dirasakan biasanya sulit untuk didiagnosa sendiri oleh masyarakat awam, sehingga sulit bagi masyarakat melakukan tindakan pencegahan. Paper ini menyajikan model sistem pakar berbasis Web untuk mendiagnosa secara dini Covid-19 menggunakan Metode Case Based Reasoning untuk membantu masyarakat mendiagnosa dini Covid 19. Pengujian aplikasi dilakukan dengan membandingkan hasil diagnosa aplikasi sistem pakar dengan pendapat pakar. Hasil uji terhadap 6 sampel kasus menunjukkan aplikasi dapat mendignosa keseluruhan kasus sesuai pedapat pakar.Kata kunci: Sistem Pakar, COVID-19, Case Based Reasoning